Lived experience research in learning disabilities: The understanding inequalities project from a service user's perspective. - Gray, Ben; Kerridge, Tom (British Journal of Learning Disabilities, 2023)
Background: People with learning disabilities are often left behind and ostracised in life, education, employment and in research. This article describes the importance and value that people with learning disabilities can bring when participating in co‐production and lived experience research. The article reports on the inequalities and barriers that people living with learning disabilities have in accessing health and social care services and hospitals and makes recommendations for improving services and people's experiences of services. The intertwining of subject (inequalities and barriers of access) and process (lived experience research and co‐production) leads to more comprehensive knowledge and understanding of learning disabilities. Methods: Co‐production events were held with people with learning disabilities, facilitated by the co‐author (Tom Kerridge). Tom and a service user researcher (Ben Gray) with Asperger's syndrome and schizophrenia thematised transcripts and made recommendations, in Ben's case with the insight of lived experience of learning disabilities and mental health problems. Findings: A series of recommendations are made based on the insight of a lived experience perspective. For example: to have a grass roots learning disabilities champion, lived experience peer mentors and supporters, training via a film made by people with learning disabilities, the involvement of Learning Disabilities Research Ambassadors to conduct phase two of the research as well as other recommendations. Conclusions: Lived experience research and co‐production are at the heart and centre of contemporary research in health and social care. Participation can change feelings of exclusion and stigma into feelings of being valued, accepted and being able to make a difference. Accessible summary: People with learning disabilities and mental health problems (like Ben), can feel left behind, like they do not fit in, do not belong and that their chances in life are limited.People can feel that they do not matter, have no voice or say, and that they are forgotten. People with learning disabilities, in Ben's own personal experience, can feel not listened to, looked down on and can face bullying.This paper is about the value that people living with learning disabilities can bring to research and help make health and social care services better.